The Fifth Dialog State Tracking Challenge - Kim, Seokhwan; D’Haro, Luis Fernando; Banchs, Rafael E.; Williams, Jason; Henderson, Matthew; Yoshino, Koichiro (Proceedings IEEE Spoken Language Technologies Workshop, 2016)
Dialog state tracking – the process of updating the dialog state after each interaction with the user – is a key component of most dialog systems. Following a similar scheme to the fourth dialog state tracking challenge, this edition again focused on human-human dialogs, but introduced the task of cross-lingual adaptation of trackers. The challenge received a total of 32 entries from 9 research groups. In addition, several pilot track evaluations were also proposed receiving a total of 16 entries from 4 groups. In both cases, the results show that most of the groups were able to outperform the provided baselines for each task.